Występowanie sytuacji meteorotropowych w Polsce w latach 2000-2020 - Chabowska, Monika; Kolendowicz, Leszek; Półrolniczak, Marek (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
Meteotropic situations are defined as weather that may affect human health and exacerbate diseases, especially in sensitive persons. The main objective of the paper is to determine the occurrence of meteotropic situations in Poland in years 2000–2020. The study took into account the characteristic elements such as very hot days (tmax> 30°C), frosty days (tmax< 0°C), day-to-day changes of mean daily air temperature (Δtśr> 6°C), day-to-day changes of mean daily air pressure (≥ 8 hPa) and days with insolation deficit. The research indicated that the highest heat stress strain is typical of the western and central parts of Poland and the highest low air temperature stimuli intensity of high mountain regions. Then, the highest fluctuations of the air temperature interdiurnal variation are characteristic of high mountain regions with the air pressure interdiurnal changes typical of the coastal region. According to our research, the most frequent meteotropic situation was associated with the insolation deficit occurring mostly in the north-eastern and high mountain regions of Poland.